A comparison of polymer and polymer–hydroxyapatite composite tissue engineered scaffolds for use in bone regeneration. An in vitro and in vivo study. Issue 8 (5th September 2013) - Tayton, E.; Purcell, M.; Aarvold, A.; Smith, J. O.; Briscoe, A.; Kanczler, J. M.; Shakesheff, K. M.; Howdle, S. M.; Dunlop, D. G.; Oreffo, R. O. C.
Abstract Previous in vitro work demonstrated porous PLA and PLGA both had the mechanical strength and sustained the excellent skeletal stem cell (SSC) growth required of an osteogenic bonegraft substitute, for use in impaction bone grafting. The purpose of this investigation was to assess the effects of the addition of hydroxyapatite (HA) to the scaffolds before clinical translation. PLA, PLA+10% HA, PLGA, and PLGA+10% HA were milled and impacted into discs before undergoing a standardized shear test. Cellular compatibility analysis followed 14 days incubation with human skeletal stems cells (SSC). The best two performing polymers were taken forward for in vivo analysis. SSC seeded polymer discs were implanted subcutaneously in mice. All polymers had superior mechanical shear strength compared with allograft (p < 0.01). Excellent SSC survival was demonstrated on all polymers, but the PLA polymers showed enhanced osteoblastic activity (ALP assay p < 0.01) and collagen‐1 formation. In vivo analysis was performed on PLA and PLA+10% HA. MicroCT analysis revealed increased bone formation on the PLA HA (p < 0.01), and excellent neo‐vessel formation in both samples. Histology confirmed evidence of de novo bone formation. PLA HA showed both enhanced osteoinductive and osteogenic capacity. This polymer composite has been selected for scaled‐up experimentation before clinical translation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2613–2624, 2014.